Transduodenal-transpapillary endopancreatic surgery with a rigid resectoscope: experiments on ex vivo, in vivo animal models and human cadavers - Müller, Philip C.; Steinemann, Daniel; Nickel, Felix; Chinczewski, Lukas; Müller, Beat P.; Linke, Georg R.; Z’graggen, Kaspar (Surgical endoscopy and other interventional techniques, 2017)
BackgroundSurgery for chronic pancreatitis is afflicted with high morbidity. A novel transduodenal-transpapillary endopancreatic resection (EPR) may provide a less invasive alternative approach.Materials and MethodsAfter laparoscopic duodenotomy the papilla was dilated and accessed with a rigid resectoscope. A resection of pancreatic head tissue was performed from inside the organ. First, the feasibility and resection volume were assessed in bovine pancreas. Bleeding and intraoperative complications were evaluated in an acute in vivo pig model. Finally, the total laparoscopic approach was tested in human cadavers.ResultsEPR was feasible in 6/6 bovine and 5/6 porcine pancreases; in one case the papilla could not be located. The resected surface accounted for 30 (23-39)% of the total pancreatic surface and the resection volume was 14.2 (9-25) cm3. In vivo blood loss was minimal [10 (5-20) ml]. The operating time for EPR was 84 (75-110) min in all cadavers.ConclusionThe EPR technique is feasible and provides a resection comparable with duodenum-preserving pancreatic head resection (DPPHR). Given the reduced surgical trauma, EPR may emerge as a minimally invasive alternative to DPPHR.